2004
DOI: 10.1177/0047287503258841
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Perceived Value Dimensions: Implications for Hospitality Research

Abstract: The proposition that guides this article is that value for money not only influences customers’ choice behavior at the prepurchase phase but also affects their intention to recommend and return behavior at the postpurchase phase. Perceived value is conceptualized as consisting of two dimensions: acquisition value and transaction value. The study applied a two-dimensional value scale developed by Grewal, Monroe, and Krishnan to hospitality services; hotels, and restaurants. Although the scale was found to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 26 publications
4
91
0
3
Order By: Relevance
“…In concurrence with H3, the results confirmed that an inverse relationship exists between perceived price and purchase intention. This finding is in line with the results from, for example, Magnusson et al (2001) and Al-Sabbahy et al (2004) and it supports the notion that premium pricing of organic food is one of the key reasons that discourage consumers from developing positive purchase intentions for such produces.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In concurrence with H3, the results confirmed that an inverse relationship exists between perceived price and purchase intention. This finding is in line with the results from, for example, Magnusson et al (2001) and Al-Sabbahy et al (2004) and it supports the notion that premium pricing of organic food is one of the key reasons that discourage consumers from developing positive purchase intentions for such produces.…”
Section: Discussionsupporting
confidence: 90%
“…Price consciousness Generally, organic products are charged at a higher price. This has essentially been the greatest and paramount reason for consumers' failure to develop positive purchase intentions toward organic food (Magnusson et al, 2001;Al-Sabbahy, Ekinci & Riley, 2004). Padel & Foster, (2005) suggests that consumers require value for their money so as to justify the price premium being paid.…”
Section: Figure: Relative Prominence Of Food Vulnerabilities For Humamentioning
confidence: 99%
“…Woodruff (1997) defines customer value as 'a customer's perceived preference for and evaluation of those product attributes, attribute performances, and consequences arising from use that facilitate (or block) achieving the customer's goals and purposes in use situations ' (p. 142). In line with this focus, research has delineated perceived experience value in various tourism contexts, such as hospitality (Al-Sabbahy et al, 2004;Kashyap and Bojanic, 2000), heritage tourism (Chen and Chen, 2010), cruise experiences (Duman and Mattila, 2005;Petrick, 2004), golf tourism (Hutchinson et al, 2009;Petrick and Backman, 2001), dining experiences (Oh, 2000), vacation purchase situations (Sánchez et al, 2006), adventure tourism (Williams and Soutar, 2009), visitor centres and tourist attractions (Prebensen et al, 2013a;Prebensen et al, 2013b), and among timeshare owners (Bradley and Sparks, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The other areas of service most commonly investigated are restaurants (e.g. Wu & Liang, 2009;Jensen & Hansen, 2007;Al-Sabbahy, Ekinci & Riley, 2004;Tam, 2000), transportation (e.g. Park, 2007;Ho, Chung, Lin & Chuen, 2010) and entertainment/activities (e.g.…”
Section: Published By Scholink Co Ltdmentioning
confidence: 99%
“…In last decade, there have been several studies investigating the different dimensions of value in tourism (Babin & Kim, 2001;Petrick, 2002Petrick, , 2003Al-Sabbahy, Ekinci & Riley, 2004;Duman & Mattila, 2005;Sánchez et al, 2006;Feng & Morrison;Gallarza & Gil, 2006;Sparks, Butcher & Bradely, 2008;Williams & Soutar, 2009;Wu & Liang, 2009;Kim, Kim and Goh, 2011). Many of these researchers have used or adapted the scales and/or typologies that have been applied outside of tourism (e.g.…”
mentioning
confidence: 99%